PENERAPAN “LIVE” SMART CITY KOTA TANGERANG - Didi Kurnaedi (Jurnal TAM (Technology Acceptance Model), 2017)
LIVE City is a smart city concept that can help people manage the available resources efficiently and provide accurate information to the public or agencies in conducting its activities or events that I will expect the unexpected. Smart city is a dream of almost all countries in the world. With LIVE City, a variety of data and information that reside in every corner of the city can be collected via sensors mounted in each corner of the city, were analyzed by the intelligent application, then presented in accordance with the needs of users with applications that can be accessed by a variety of means. Through gadgets, interactive user can also be a source of data, they send information to the data center for use by other users. The aim of this study was to assess the progress and analyze the strengths and weaknesses of the information system LIVE that have been applied using PIECES Framework, as well as to determine whether there is an impression of the level of profit increase in the use of the system so that companies can make follow-up of leads business to face the global challenges. The method used is the method PIECES Analysis Framework, which consists of multiple point analysis, namely: Performance, Informations and Data, Economics, Control and Security, Efficiency, and Service. Where each point of the analysis is the evaluation and analysis reference information system. The results showed that the information system is being used by Play already has a number of advantages and strengths that can support operational activities LIVE, but there are also some weaknesses and shortcomings so that the system still needs to be improved LIVE information.